Coding and regulatory transcriptome comparisons between fertile and infertile spermatozoa identify RNA signatures of male infertility. (18th April 2022) - Joshi, Meghali; Andrabi, Syed Waseem; Singh, Vertika; Bansal, Sandeep Kumar; Makker, Girish Chandra; Mishra, Geetanjali; Gupta, Gopal; Rajender, Singh
Abstract: The aim of the present study was to identify RNA‐based signatures of male infertility by sperm transcriptome analysis. In this study, deep sequencing analyses of coding (mRNA) and regulatory (miRNA) transcriptomes were performed by pooling 15 oligo/oligoasthenozoospermic infertile sperm and 9 normozoospermic fertile sperm samples. Furthermore, interesting candidates were selected for validation by real‐time PCR. The comparison of miRNAs between cases and controls identified 94 differentially expressed miRNAs, of which at least 38 have known functions in spermatogenesis. In transcriptome (mRNA) data, a total of 60, 505 transcripts were obtained. The comparison of coding RNAs between cases and controls revealed 11, 688 differentially expressed genes. miRNA–mRNA paired analysis revealed that 94 differentially expressed miRNAs could potentially target 13, 573 genes, of which 6419 transcripts were actually differentially expressed in our data. Out of these, 3303 transcripts showed inverse correlation with their corresponding regulatory miRNAs. Moreover, we found that most of the genes of miRNA–mRNA pairs were involved in male germ cell differentiation, apoptosis, meiosis, spermiogenesis and male infertility. In conclusion, we found that a number of sperm transcripts (miRNAs and mRNAs) have a very high potential of serving as infertility/sperm quality markers.